IMPLEMENTASI TAFTISYUL KUTUB DALAM MENINGKATKAN PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DI SMP AL-RIFA'IE GONDANGLEGI KELAS DELAPAN - Rosida Chaulatul Jariyah; Muhamad Hanief; Devi Wahyu Ertanti (Vicratina : Jurnal Ilmiah Keagamaan, 2020)
Boarding school at this time not only provide religious educational institutions, but in the boarding school there are also formal education institutions. The Problem faced by Al-Rifa'ie SMP is one of the disobedience of learners in the task that has been given by the teacher. The purpose of the research is describing the planning, implementation and evaluation of the pole Taftisyul Kutub in SMP Al-Rifa'ieaccording To Analysis of data obtained then it can be known planning test pole Taftisyul Kutub in SMP AL-Rifa'ie begins with the establishment of the exam committee of Taftisyul Pole. The Taftisyul Examination Committee of the Polar is tasked with preparing everything needed for the examination of Taftisyul poles. The results of this researcher's conclusion shows that the Taftisyul exam is the strategy used by SMP Al-Rifa'ie to minimize the disobedience of students at Al-Rifa'ie SMP. The Taftisyul exam is performed once a Semestaer, held before the written exam. As the pole Taftisyul takes place students must complete all the books they use during a semester. Students who have fulfilled the criteria of Taftisyul polar exam He got a pass card sign of Taftisyul pole exam.